Public Network Models: A Typology Based on a Systematic Literature Review - Barczak, Beata (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2024)
Objective: The article develops, based on a systematic literature review (SLR), a typology of public network models. It interprets the concept and specificity of a public network. Finally, it reviews the typology of organisational network models and indicates the directions for further research.Research Design & Methods: The methodology of systematic literature review was used, supplemented by snowball sampling. To obtain data, the Scopus and Web of Science (WoS) scientific databases were analysed. The results were then synthesised to develop a typology for public networks. Typological analysis was used in addition to SLR and snowball sampling.Findings: As a result of a systematic review of the literature, a typology of public network models was reviewed and a typology proposed. The theoretical function of the typology is an indication of trends in the development of public network models, while its practical function is as a tool for further analysis.Implications / Recommendations: The analysis shows that public networks differ from other networks, such as business networks. The breakdown of public network models is multi-layered and may include various criteria. The typology developed for the paper covers four types of public networks: global public networks, networks of public organisations, local government networks, and partnerships.Contribution: The issues discussed in the paper fill the research and methodological gap in research on public networks. This gap is a stark lack of theory and conceptualisation in studying such networks. The paper defines the role of the network approach as an emerging paradigm in the management of the public sphere, and that is its main contribution.